Comparison of computational and experimental analysis for a laboratory-sized cyclone separator testbed - Chua, Bih Lii; Wong, H. L.; Mohd Suffian, Misaran; Tong, Tshen Jui (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Applications and Design in Mechanical Engineering 2012 (ICADME 2012) organized by School of Mechatronic Engineering, Universiti Malaysia Perlis (UniMAP), 27th - 28th Februari 2012 at Bayview Beach Resort, Penang, Malaysia.